High circulating proprotein convertase subtilisin/Kexin type 9 concentration associates with cardiovascular risk: A meta-analysis of cohort studies. Issue 48 (December 2017) - Qiu, Chengfeng; Zhou, Quan; Li, Xiaohui; Zhang, Zhen; Zeng, Pingyu; Cao, Zeng; Pan, Bingjie; Li, Xiaogang; Chen, Alex F.
Abstract : Abstract: Whether the baseline circulating proprotein convertase subtilisin/Kexin type 9 (PCSK9) concentration associates with cardiovascular risk remains uncertain. This study aimed to investigate the predictive value of circulating PCSK9 in cardiovascular risk prediction. Relevant studies were searched through the MEDLINE, EMBASE, and Cochrane Library databases. The relative risk (RR) and 95% confidence interval (CI) were pooled to evaluate the association between the circulating PCSK9 concentration and cardiovascular risk. Dose–response meta-analysis was also performed in this study. A total of 11 cohort studies with 13, 761 participants were included. The RR for cardiovascular risk was 1.25 (95% CI: 1.14–1.38, P  < .001, I 2  = 25%) while compared highest to lowest PCSK9 concentration. Subgroup meta-analysis, which sorted by ethnicity, base risk characteristic, and follow-up time, presented consistent results that there was a pronounced association between highest PCSK9 concentration and cardiovascular risk, such relationship was not significant in the statin-taking subjects. Seven studies were included in dose–response meta-analysis, and a nonlinear association between PCSK9 concentration and cardiovascular risk was observed [(χ 2 test for nonlinearity = 6.7, ( df  = 2), P  = .036]. This study suggests that high circulating PCSK9 concentration associates with significantly increased cardiovascular risk, and demonstrates for the first time that it is a nonlinear dose–response association between circulating PCSK9 concentration and cardiovascular risk. These results provide the evidence that PCSK9 is an independent risk factor beyond the traditional cardiovascular risk factors and indicates a potential role of PCSK9 measurement for medical decisions. The clinical value of PCSK9 measurement and the identification of risk threshold should be confirmed in appropriately designed clinical trials. Abstract : Supplemental Digital Content is available in the text